Role of soil bacterial consortia on glyphosate degradation and growth of maize seedlings - Reginawanti Hindersah; Probo Condrosari; Aten Komarya; Pujawati Suryatmana; Oviyanti Mulyani; Harry Rum Haryadi (Journal of Degraded and Mining Lands Management, 2021)
Pre-growing weed control by glyphosate herbicides is effective for increasing yield, but glyphosate residues in the soil might reduce soil quality and can accumulate in agricultural products. Naturally, microbes are able to breakdown glyphosate into nontoxic substances orthophosphate and glycine. Glyphosate degradation in soil by single soil microbes are reported elsewhere, but the information about glyphosate removal by soil bacterial consortia was limited. The objective of this research was to determine the effect of carbon (C), nitrogen (N), and phosphorus (P) composition in liquid media to increase glyphosate degradation and its degradation product by soil bacterial consortia and 2) verify the effect of bacterial consortia on maize seedlings growth, their N and P uptake, as well as total and soluble P in soil. Glyphosate degradation test was set up by incubating bacterial consortia in a different composition of C-N-P liquid basal media. Greenhouse experiment has been performed in a randomized block design to treat maize grown in Inceptisols with bacterial and glyphosate application. The results showed that C-N-P composition of liquid media affected the concentration of glyphosate, as well as orthophosphate and glycine as by-products. In-planta experiment verified that inoculation of glyphosate-degrading bacterial to maize seedling grown in glyphosate-contaminated soil enabled to enhance shoot dry weight of maize seedling and N and P uptake at 4 weeks after inoculation.